Designing a uniform for female sewers of selected Metro Manila companies. - Gilpo, Dellet R.
The study aimed to develop a design for a uniform female sewers of selected Metro Manila garment companies. Data gathered from the review of related literature yielded a functional design process and strategy selection which was employed in this study. The managers of six companies, three of them require uniforms and the other three do not, were interviewed about the views of the management on the use of uniforms in the workplace. Sewers were given questionnaire which solicited from them their opinions on uniforms and their preferences in the features of the uniforms. It was found out that majority of the sewers, eighty-eight percent wanted to have uniforms and that these uniforms should be comfortable, decent, pleasing to the eyes, would not hamper movement, will suit the wearer's age and inexpensive to produce. A blouse with button front opening and convertible collar, and a pair of cullotes with inverted box pleats were created as a result of the analysis of the data gathered and from the review of literature. The desired characteristics of the sewers and the management and the job requirement were incorporated in the design of the uniform. The objectives of the study which were to develop a design for a uniform which is --- 1) inexpensive to produce; 2) comfortable for the wearer; 3) promote a professional appearance; 4) will not hamper with work; and 5) with sizes that all figure types were met by the prototype requirements. It was developed with the design criteria and objectives in consideration.